Analisis Perawatan Mesin Las Titik Dengan Metode Failure Mode And Effect Analisys (FMEA) di PT. XYZ: Maintenance Analysis of Spot Welding Machines With Failure Mode And Effect Analyses (FMEA) Method in PT. XYZ - Yunisa Rahmawati; Kardiman; Oleh (Jurnal Pendidikan Teknik Mesin Undiksha, 2024)
The rapid development of the industrial world has resulted in increased competition in the industrial world, so companies are competing to improve the quality and quantity of production. A company's effort in increasing the amount of production is to extend the operation of industrial facilities and reduce company expenses caused by damage to production facilities, one of which is engine damage. Machinery is an important means in a production process in the company. PT XYZ is a private company engaged in the manufacture of metal stamping parts, tools, and dies for the manufacture of car staping parts. This study aims to analyze the maintenance of spot welding machines with the   Faillure Mode And Effect Analysis (FMEA) method. Maintenance is all activities needed to maintain the quality of equipment or machinery to keep it functioning properly and keep the facility or equipment always in a ready-to-use state. Failure Mode And Effect Analysis (FMEA) is a method for evaluating the possibility of failure of a system, design, process or service to create handling steps. From the analysis of the RPN calculation on the spot welding machine, the overall result is 919. This value exceeds the standard welding machine maintenance set with the overall RPN value must be below 400. A high RPN value indicates a low level of reliability on the tool. Keywords : FMEA, Maintenance, Spot Welding, Welding.